Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbantuan Canva yang Efektif - Said, Fadilla Fadya; Susanto, Andi; Utami, Nita Putri (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2023)
Abstract This study aimed to develop Canva-assisted Student Worksheets (LKPD) for eighth-grade students at MTsN 5 Padang City, focusing on enhancing their understanding of concepts in relations and functions. The research followed the Plomp model, involving three phases: initial investigation, prototype development, and evaluation. Questionnaires, interviews, and tests were used to measure validity, practicality, and effectiveness. Data analysis employed descriptive statistics. The results of the Canva-assisted LKPD development showed high validity, with a content, language, and presentation score of 93.02%. The LKPD also demonstrated practicality, achieving 87.77% and 89.39% scores from students' and teachers' perspectives, respectively. Factors like ease of use, time efficiency, attractiveness, comprehension, and alignment with the curriculum were considered. Additionally, the LKPD was effective, as 87.5% of students scored above the Minimum Mastery Criteria (KKM) in concept comprehension tests. Utilizing Canva in LKPD development successfully created an engaging product that improved students' understanding of mathematical concepts in relations and functions. The data collection method supported these findings, indicating that Canva-assisted LKPD enhances students' comprehension. The test results revealed that 28 out of 32 students (87.5%) achieved scores above the KKM threshold, categorizing them as "highly successful." The validation of Canva-assisted LKPD confirmed high validity in terms of presentation, language, and media aspects. Overall, the LKPD was considered "highly practical" and had the potential to enhance motivation and the effectiveness of mathematics learning. Therefore, the utilization of Canva-assisted LKPD offers an effective alternative for improving students' understanding of mathematical concepts. Keywords: LKPD, Canva, Understanding Mathematical Concepts, Plomp Model.